How must pH affects the level of red wine phenols. (July 2020) - Forino, Martino; Picariello, Luigi; Rinaldi, Alessandra; Moio, Luigi; Gambuti, Angelita
Abstract: Slight variations of pH affect the sensory properties and stability of wines with important implications for the winemaking practices. Preliminary studies in wine-like solutions with pH values ranging from 3 to 4 showed that anthocyanin solubility decreased as the pH increased. A significant drop of solubility was observed at pH 3.3. In order to verify these results in real wines, an experimental protocol was designed with the purpose of investigating the pH influence on the anthocyanin extractability in three musts differing from each other only by the pH levels adjusted to 3.2, 3.5 and 3.9, respectively. The NMR-based analysis of the wines, deriving from the three musts, provided data consistent with those observed in wine-like solutions. The extraction of anthocyanins turned out to be increasingly lower as the pH increased even if the effect of pH was more contained than expected on the basis of the data obtained from model solutions. Other molecules of enological interest, mainly catechins and cinnamates, were proven to be affected by the must pH. Additionally, tannins slightly increased as the pH increased but the reactivity of tannins towards saliva decreased confirming the decisive role of pH also on wine astringency. Graphical abstract: Image 1 Highlights: pH is crucial to red wine longevity: the higher the pH the less stable the wine. As the pH increases, the concentration of anthocyanins decreases. As the pH increases, the concentration of flavan-3-ols increases. At high pH values, red wines are naturally less protected against oxidation.